2022
DOI: 10.1177/10659129221114049
|View full text |Cite
|
Sign up to set email alerts
|

Media Attention and Deliberation on the Supreme Court

Abstract: The news media acts as a “watchdog” over political institutions by holding them accountable for their actions through critical commentary. Being that the Supreme Court rarely interacts directly with the public, the news media is the primary mechanism through which individuals become aware of the Supreme Court’s actions and decisions. Thus, for the Supreme Court, the news media’s role as a “watchdog” takes greater meaning than it does for institutions that often speak directly to the public. Considering this, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…More recently, Ono and Zilis (2022) found that female and Hispanic judges are stereotyped to be biased in favor of their ingroup and thus less able to rule fairly in immigration and abortion cases. Badas and Justus (2023) find that respondents that believed there to be more millionaire Justices on the Supreme Court were more inclined to state the Court was less legitimate and biased in favor of the wealthy. Scholars have also addressed the ways in which judicial scandal can shape perceptions of legitimacy.…”
Section: Judicial Impartialitymentioning
confidence: 83%
“…More recently, Ono and Zilis (2022) found that female and Hispanic judges are stereotyped to be biased in favor of their ingroup and thus less able to rule fairly in immigration and abortion cases. Badas and Justus (2023) find that respondents that believed there to be more millionaire Justices on the Supreme Court were more inclined to state the Court was less legitimate and biased in favor of the wealthy. Scholars have also addressed the ways in which judicial scandal can shape perceptions of legitimacy.…”
Section: Judicial Impartialitymentioning
confidence: 83%
“…Additional research could also assess how the public responds when partisan cues compete with other types of informational cues (for example, a cue priming concerns of procedural fairness). In particular, within a polarized media environment, the cues to which citizens are exposed based on their media consumption may play a critical role in how they ultimately perceive legal actors (Badas & Justus, 2023;Baird & Gangl, 2006;Hoekstra, 2003;Zilis, 2015). This represents a fruitful avenue for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reality of the coverage, Supreme Court justices attempt to use the mediaworthy parts of their opinion to convey the legal soundness of their decisions and move focus away from outcomes. They approach cases with greater media coverage with more care, taking longer to write opinions and producing more cognitively complex ones too (Badas and Justus 2022). The justices can also use the opinion writer to cue legal soundness.…”
Section: Supreme Court Opinions and The Publicmentioning
confidence: 99%